STRENGTHENING THE LEGALITY AND STANDARDIZATION OF WAHYU ALAM TRADITIONAL HERBAL PRODUCTS FOR THE GLOBAL MARKET: AN INDONESIA–VIETNAM COLLABORATION - Putra, Restu Adi; Tam, Tong Hung; Ly, Chan Thi; Windaradi, Fitri; Putri, Nurfatri (Universitas Kadiri, 2025)
This international community service program was implemented to improve the legality and standardization of Wahyu Alam traditional herbal products so they are ready to penetrate the global market. The methods used included product legality training (PIRT, Halal, HACCP), packaging design workshops, assistance in preparing export documents (CoA, MSDS), and international discussions with Vietnamese partners. Results showed significant improvements in legal understanding, environmentally friendly packaging innovation, and international networking. Collaboration with the Vietnam Herbal Association resulted in a Letter of Intent (LOI) with two distributors in Ho Chi Minh City as a first step towards export. This program demonstrates that intensive mentoring and international collaboration can increase the competitiveness of Indonesian herbal MSMEs in the ASEAN market.